A Solar Photovoltaic Performance and Financial Modeling Solution for Grid-Connected Homes in Zambia - Katundu Imasiku (International Journal of Photoenergy)
Zambia is today 90% hydropower dependent, but this may change because Zambia and the World at large are today facing a changing climate that affects the ecosystem, rain patterns, and spurs drought which reduces the production of hydropower. The current power deficit experienced in Zambia points to a need to deploy a renewable energy generation-mix strategy. This study conducts a solar photovoltaic performance and financial analysis for grid-connected homes in Zambia to investigate the role of solar energy as an enabler for energy security in Zambia using the National Renewable Energy Laboratory (NREL) System Advisor Model (SAM) simulation method. It further reviews the available solar irradiance, modeling a detailed grid-connected photovoltaic system using locally available products for a single owner in a power purchase agreement (PPA) with the Zambia Electricity Company Limited (ZESCO). This model would alleviate the current power load shedding experienced by the residential sector, of up to 22 hours of no electricity out of 24 hours in a day. Alongside the technical performance model and an unfavorable business climate in Zambia, a financial model is also developed to help assess project feasibility and financial viability. A 1 kW solar PV system was modeled at an installation cost of US$1.27 per watt on a short-term basis of 5 years and found that the project is feasible with a 28.52% IRR achieved in 3 years and a 69% performance ratio and a debt service coverage ratio (DSCR) of 5.12 by the end of the project life, thereby indicating capability to turn around Zambia’s energy poverty to meet the UN SDG 7.